PERSEPSI PETANI TERHADAP KINERJA PENYULUH PERTANIAN MENURUT INDIKATOR KAPASITAS PETANI DAN TEKNOLOGI INFORMASI PERTANIAN - syamsir, syamsir; abidin, zainal; jafar, muh iqbal; jafar, isran (Jurnal Agristan, 2024)
One of those who play a role in agricultural development in Indonesia is agricultural extension agents through the programs and activities carried out. However, farmers with various patterns of attitudes and thoughts have different perceptions in seeing agricultural extension workers. The purpose of this study was to determine the perception of farmers based on 2 indicators assessed. This research was conducted in Sidodadi Village, Sangkub District, North Bolaang Mongondow Regency. The data collection method used is the method of observation and questionnaire interviews with a list of statements that have been prepared. The number of respondents in this study amounted to 65 farmers. The results of the study indicate that the perception or assessment of farmers based on the farmer capacity indicator is in a good category with a score of 213.2 with a percentage of 65.60%, while for agricultural technology information indicators are also in a good category, with a score of 201.6 with a percentage of 62, 03%. So, based on the 2 indicators assessed, farmers' perceptions are included in the good category with an average score of 1037 with an index score of 63.82%.